2017
DOI: 10.1155/2017/3537026
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Turbulence Models for Numerical Simulation of Pressure Distribution in V-Shaped Stepped Spillway

Abstract: V-shaped stepped spillway is a new shaped stepped spillway, and the pressure distribution is quite different from that of the traditional stepped spillway. In this paper, five turbulence models were used to simulate the pressure distribution in the skimming flow regimes. Through comparing with the physical value, the realizable -model had better precision in simulating the pressure distribution. Then, the flow pattern of V-shaped and traditional stepped spillways was given to illustrate the unique pressure dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
(16 reference statements)
1
9
0
Order By: Relevance
“…The results revealed that the realizable k-ε model is the most efficient. The same result was reported in the literature as well [26,30,43,44].…”
Section: Velocity Distributionsupporting
confidence: 90%
“…The results revealed that the realizable k-ε model is the most efficient. The same result was reported in the literature as well [26,30,43,44].…”
Section: Velocity Distributionsupporting
confidence: 90%
“…Mohammad et al [37] used the VOF model and the turbulence models RNG and LES to simulate the interaction between air and water using stepped spillway models with a steep slope. Bai and Zhang [38] simulated a different type of stepped spillway called the V-type stepped spillway. They analyzed the pressure distribution by five different turbulence models and compared it with the physical values.…”
Section: LImentioning
confidence: 99%
“…Performing CFD simulations is an effective tool to study complex flow problems [23][24][25][26]. Previous CFD studies [21,[27][28][29] reported the capability of the k − ε model in reproduction of the major hydraulic characteristics of the flows over stepped spillways. erefore, in the current study, this turbulence model by Launder and Spalding [30] is used to look into the spillway flow features with different step layouts.…”
Section: Numerical Modelmentioning
confidence: 99%